Trypanosomatid Pin1-type Peptidyl-Prolyl Isomerase is Cytosolic and Not Essential for Cell Proliferation - Erben, Esteban Daniel (2012)
Pin1-type peptidyl-prolyl cis/trans isomerases (PPIases) isomerise the peptide bond of specific phosphorylated (Ser/Thr)-Pro residues, regulating various cellular events. Previously, we reported a Pin1-type PPIase in Trypanosoma cruzi, but little is known about its function and subcellular localization. Immunofluorescence analysis revealed that in contrast with Pin1-like proteins from diverse organisms, TcPin1 mainly localized in the cytoplasm and was excluded from the nuclei. In addition, RNAi-mediated downregulation of TbPin1 in Trypanosoma brucei did not abolish cell proliferation. Using yeast two-hybrid assay, we identified a MORN domain-containing protein as putative Pin1-binding partners. These data suggest that Pin1-mediated signaling mechanism plays a different role in protozoan parasites.